Enzymes involved in organellar DNA replication in photosynthetic eukaryotes - Moriyama, Takashi; Sato, Naoki (Frontiers in Plant Science, 2014)
Plastids and mitochondria possess their own genomes. Although the replication mechanisms of these organellar genomes remain unclear in photosynthetic eukaryotes, several organelle-localized enzymes related to genome replication, including DNA polymerase, DNA primase, DNA helicase, DNA topoisomerase, single-stranded DNA maintenance protein, DNA ligase, primer removal enzyme, and several DNA recombination-related enzymes, have been identified. In the reference Eudicot plant Arabidopsis thaliana, the replication-related enzymes of plastids and mitochondria are similar because many of them are dual targeted to both organelles, whereas in the red alga Cyanidioschyzon merolae, plastids and mitochondria contain different replication machinery components. The enzymes involved in organellar genome replication in green plants and red algae were derived from different origins, including proteobacterial, cyanobacterial, and eukaryotic lineages. In the present review, we summarize the available data for enzymes related to organellar genome replication in green plants and red algae. In addition, based on the type and distribution of replication enzymes in photosynthetic eukaryotes, we discuss the transitional history of replication enzymes in the organelles of plants.